The impact of an exercise intervention on frailty levels in hospitalised older adults: secondary analysis of a randomised controlled trial. (18th February 2022) - Pérez-Zepeda, Mario Ulises; Martínez-Velilla, Nicolás; Kehler, Dustin Scott; Izquierdo, Mikel; Rockwood, Kenneth; Theou, Olga
Abstract: Background: physical activity reduces frailty in community-dwelling older adults. How exercise influences frailty in hospitalised older adults requires additional investigation. Objectives: (i) to examine the impact of an exercise intervention on frailty in older adults admitted to an acute care ward, and (ii) to determine the impact of baseline frailty on the effectiveness of this intervention. Setting/participants: this is a secondary analysis of a randomised controlled clinical trial that tested an intensive exercise intervention in ≥75-year-old adults admitted to an acute care ward. Methods: the intervention included two daily sessions of moderate-intensity exercises (control received usual care). A 63-item Frailty Index (FI) was constructed, and three groups were formed: <0.2, 0.2–0.29 and ≥0.3. Other outcomes included Short Physical Performance Battery (SPPB) and Barthel Index (BI). Results: a total of 323 individuals were included. The mean age was 87.1 years (± 4.8 standard deviation [SD]) and 56.3% were females. The intervention group improved FI from 0.26 (± 0.10 SD) to 0.20 (± 0.10 SD), whereas the control group FI worsened from 0.25 (± 0.1 SD) to 0.27 (± 0.10 SD). After stratifying by baseline FI, SPPB and depression improved in the intervention group across all levels of frailty; FI, BI and quality of life only improved in individuals with a baseline FI ≥ 0.2. Conclusions: frailty improves with an intensive individualised exercise intervention, especially in those with high baseline levels of frailty. In addition, frailty is a useful outcome when examining the impact of an intervention of hospitalised older adults.